2007
DOI: 10.1017/s1041610207005625
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of dementia among older adults from poor socioeconomic backgrounds in São Paulo, Brazil

Abstract: The prevalence of dementia among older adults from low socioeconomic backgrounds is high. This may be partly due to adverse socioeconomic conditions and consequent failure to compress morbidity into the latter stages of life. The increasing survival of poorer older adults with dementia living in developing countries may lead to a rapid increase in the prevalence of dementia worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1
38

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 33 publications
10
112
1
38
Order By: Relevance
“…For each study and age group, prevalence and 95% confidence intervals were calculated using the GraphPad StatMat Version 1.0 software. The standardized prevalence of dementia according to age was calculated using as the standard population the global world population in 2000 (United Nations Department of Economic and Social Affairs, 2005), following the method used by Scazufca et al (2008). In each case, the standardized prevalence may be seen as the estimated prevalence if the population of our study had the same age structure as the standard populations.…”
Section: Methodsmentioning
confidence: 99%
“…For each study and age group, prevalence and 95% confidence intervals were calculated using the GraphPad StatMat Version 1.0 software. The standardized prevalence of dementia according to age was calculated using as the standard population the global world population in 2000 (United Nations Department of Economic and Social Affairs, 2005), following the method used by Scazufca et al (2008). In each case, the standardized prevalence may be seen as the estimated prevalence if the population of our study had the same age structure as the standard populations.…”
Section: Methodsmentioning
confidence: 99%
“…They were recruited initially from the data base of the SPAH, 23,24 an epidemiologic investigation aimed at determining the incidence and prevalence of dementia, other mental disorders, and risk factors for these conditions. On the day of MR imaging, subjects were assessed with the Hamilton Depression Rating Scale 25 and the Global Assessment of Function Scale from the Diagnostic and Statistical Manual of Mental Disorders-IV.…”
Section: Subjects and Assessment Schedulesmentioning
confidence: 99%
“…Concerning to the mean age in the sample, the result showed a sample of younger people than that of several other studies that showed medians higher than 70 years old 5,19,[23][24][25] , despite of most of them were older than 60 years (67.5%). The study by Silva and Damasceno 9 , also in a tertiary care service showed similar results to ours.…”
Section: Discussionmentioning
confidence: 50%